Adolescent support club attendance and self-efficacy associated with HIV treatment outcomes in Tanzania - Gretchen Antelman; Ola Jahanpour; Thomas Machalo; Cosette Audi; Roland van de Ven; Mastidia Rutaihwa; Elise Lankiewicz; Sarah Baird (Public Library of Science (PLoS), 2022)
HIV treatment outcomes may be improved by ameliorating psychosocial challenges adolescents living with HIV (ALHIV) face. This analysis describes participation in existing facility-based adolescent clubs and the associations between club attendance, adolescent well-being and HIV treatment outcomes. Data were collected through interviews with a sub-sample of adolescents age 10-19 years and medical record abstraction of all adolescents attending HIV services at seven clinics in Tanzania. Independent variables included adolescent club attendance, self-esteem, self-efficacy, mental distress, social capital and other health utilization or HIV experience characteristics. Study outcomes included visit adherence, viral suppression (<1000 cp/ml), and retention. Of 645 adolescents attending HIV services, 75% attended clubs at least once with a median of eight club sessions attended over a two-year period. Mental distress was prevalent, with 67% of the adolescents scoring above a recognized cut-off of ≥5. Adolescents who attended 10 or more clubs, compared to those not attending any clubs over a two-year period were at an almost three-fold increased odds of having good visit adherence (odds ratio [OR] 2.72, 95% confidence interval [CI]: 1.25, 5.94). Club attendance was also associated with sustained retention in the following year: adolescents who attended some clubs (1-9) had three-times the odds of being retained (OR 3.01; 95%CI: 1.86, 4.87) while those who attended 10+ had over seven-times the odds (OR 7.29; 95%CI: 4.34, 12.22). Among the 154 adolescents who were interviewed, being in the top self-efficacy tertile was positively associated with viral suppression (OR 3.04, 95%CI: 1.08, 8.60) and retention (OR 4.44, 95%CI: 1.19, 17.40). Attending the HIV clinic with a guardian/treatment supporter (OR 3.29, 95%CI: 1.17, 9.22) was also associated with viral suppression. Self-efficacy, social capital and treatment support are associated with better health outcomes among adolescents. However, many ALHIV either never attended or did not regularly attend clubs.